Studies on combining ability and heterosis using cytoplasmic male sterility system in Indian mustard [Brassica juncea (L.) Czern & Coss.] - Ashutosh Kumar; Raghvendra Tiwari; Praveen Pandey and; K. Kumar (Electronic Journal of Plant Breeding, 2017)
A field experiment on Indian mustard consisting thirty two parents (two lines + thirty testers) and their sixty crosses was conducted to estimate general and specific combining ability of parents and crosses, respectively. The variances due to SCA were higher than GCA variances for almost all traits, confirming the presence of non-additive gene action in the inheritance of these characters. Among testers, NDRE-22, EJ-22, RH-919, Divya-22, NDRE-08-04, NPJ-135, PRE-2009-09, NPJ-148 and PRE-2007-06 were found good general combiners for seed yield. The crosses, CMSMori x NPJ-135 (13.17 %) and CMSNDRE-4 x PRE-2007-06 (12.83 %) showed significant sca effect and heterosis over standard varieties Kranti and Maya, respectively.